Users’ attitudes towards personal health records a cross-sectional pilot study (2016)
Background: Prevention and management of chronic conditions is a priority for many healthcare systems. Personal health records have been suggested to facilitate implementation of chronic care programs. However, patients’ attitude towards personal health records (PHRs) can significantly affect the adoption rates and use of PHRs. Objectives: to evaluate the attitude of patients with Type II diabetes towards using a PHR to manage their condition. Methods: We used a cross-sectional exploratory pilot study. Fifty-four (54) patients used a PHR to monitor and record their blood glucose levels, diet, and activities for 30 days, and to communicate with their clinicians. At the end of the study, patients responded to a survey based on three constructs borrowed from different technology acceptance frameworks: relative advantage, job fit, and perceived usefulness. A multivariate predictive model was formed using partial least squaring technique (PLS) and the effect of each construct on the patients’ attitude towards system use was evaluated. Patients also participated in a semi-structured interview. Results: We found a significant positive correlation between job fit and attitude (JF?ATT = +0.318, p less than 0.01). There was no statistical evidence of any moderating or mediating effect of other main constructs or any of the confounding factors (i.e., age, gender, time after diagnosed) on attitude. Conclusion: The attitude of patients towards using PHR in management of their diabetes was positive. Their attitude was mainly influenced by the extent to which the system helped them better perform activities and self-manage their condition. © Schattauer 2016.